Pengaruh Pemberian Dosis Pupuk Bokhasi Dan Konsentrasi Effective Mikro Organisme Lokal (MOL) : Terhadap Pertumbuhan Dan Hasil Tanaman Mentimun ( Cucumis Sativus, L ) Varietas Mercy F1 - Rukmi Budiharjo (Corolla: Jurnal Sains Pertanian, 2015)
Effect of Fertilizer Bokhasi Dose and Effective Concentration MikroOrganisme Lokal (MOL) on Growth and Crop Cucumber (CucumisSativus, L) Varieties Mercy F1. The purpose of this study was to determine the effect of fertilizer application and concentration effective bokhasi mikroorganismelokal (MOL) on the growth and yield of cucumber (Cucumissativus, L). The research was conducted in the village Gedeg, District Gedeg Mojokerto. Treatment consists of two factors, namely: Bokashi (B) which consists of three levels. B1 = 250 g / tan, B2 = 350 g / tan, B3 = 450 g / tan. The second factor is the concentration of microorganisms Local forage fresh vegetables = Mol (M) which terdiridariempattaraf. M0 = control, MOL M1 = 5 ml / liter of water, MOL M2 = 10 ml / liter of water, MOL M3 = 15 ml / liter of water. Of the two factors mentioned above there are 12 combinations of the experiment. The experiment was conducted by using a completely randomized design (CRD) which is arranged in factorial. The observation parameters vegetative growth and cucumber production is observed were: number of leaves, plant length, number of fruits, average fruit weight and length of the fruit crop. From the results of the study suggested that the growth parameters bokhasi fertilizer dosing and local microorganisms provide interaction and high value.